THE INFLUENCE OF LEADERSHIP STYLE, MOTIVATION AND DISCIPLINE ON EMPLOYEE PERFORMANCE - panggabean, naomi Frizilia; Fahri, Tm Safwan; Gunawan, Wisnu; Hendry, Hendry (International Journal of Social Science and Business, 2021)
The purpose of this study is to Test and analyze the influence of Leadership Style, Motivation and Discipline on Employee Performance at PT Sumo Internusa Indonesia. Leadership style still can encourage or motivate the employees to work more actively, effectively, efficiently and optimally. Lack of motivation of employees in the company are visible from at least giving a salary increase, a promotion, giving an increase in incentives as well as the rise of the craft of money. Employees have less work discipline of the presence of kertelambatan employees.The performance of the employees look of not achieving the target company. Methods peneltiian conducted is quantitative. The number of population and sample in this study a total of 62 employees. The simultaneous and partial leadership style, motivation and the discipline has positive and significant effect on employee performance at PT Sumo In